Pengenalan Platform dengan Menggunakan Media Wordwall di SD Inpres Morowa - Atifa, Atifa; Hajar, Andi; Suhardiman, Suhardiman (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
This service activity aims to improve the quality of learning at SD Inpres Morowa through the use of the wordwall platform. The approach used in this activity is the service learning approach. The aim of this approach is to ensure the transfer of knowledge about wordwalls to students goes well. The research method used is knowledge transfer by involving students as active participants in introductory activities. The results of this research prove that through a service learning approach, students are not only active in carrying out assignments but are also actively involved in various games and quizzes provided by the Wordwall platform. This has a positive impact on increasing student learning motivation and student learning outcomes. Apart from that, with variations in learning methods using Wordwall, students' interest in learning increases. Students show higher motivation to participate in learning and participate actively in class activities.